Impact of heat input variations on peel strength characteristics in laser wobbling micro welding a study on direct and intermittent techniques for SS304 thin sheets - Zawani, Ismail; M. M., Quazi; M., Ishak; Mohammad Amin, Ezazi; Aiman, Mohd Halil (Politeknik Sultan Abdul Halim Mu'adzam Shah, 2024)
In precision welding, laser wobbling micro welding (LWMW) has been identified as a crucial technique. It offers enhanced weld quality and minimized thermal distortion due to its ability to control the weld pool through beam oscillation. This study delves into the differential impacts of heat input variations on peel strength characteristics in LWMW, employing both direct and intermittent techniques on SS304 thin sheets, pivotal in solid oxide fuel cell interconnections. The aim is to discern the optimal welding parameters that ensure superior weld quality, focusing on peel strength and penetration characteristics, which are critical for the structural integrity and performance of the welded joints. The research methodology encompasses an experimental design where SS304 stainless steel plates are welded using a nanosecond fiber laser, with the wobble amplitude and frequency meticulously varied. Peel strength tests and penetration analysis evaluate the welding outcomes, providing a quantitative basis for comparing the direct and intermittent wobbling techniques. Results unveil a nuanced relationship between heat input and weld quality, with intermittent wobbling demonstrating superior peel strength owing to its pulsed heat input, which facilitates better thermal management, reducing thermal stress and enhancing weld integrity. Conversely, direct wobbling achieves deeper penetration due to its continuous heat application, highlighting the distinct advantages of each technique based on the desired weld characteristics. Conclusively, the study underscores the criticality of precise heat input control in laser wobbling micro welding to optimize peel strength and penetration depth. The intermittent technique, with its advantage in achieving higher peel strength, is recommended for applications requiring robust welds, while the direct method's uniform heat application suits scenarios where deep penetration is paramount. Future research should extend this analysis to encompass a broader range of materials and welding conditions, employing computational modeling to refine the understanding of heat input's role in laser wobbling welding. This exploration is poised to enhance the precision and efficiency of welding processes, supporting the advancement of manufacturing technologies in various industrial sectors.